High-energy density non-toxic cathodes based on LiMNbO4 (M = Ni, Co, Mn, Fe) composition for Li ion battery applications – density functional theory analysis - Chakrabarti, Shamik; Thakur, A. K. (Journal of materials research, 2025)
We report density functional theory studies on novel, non-toxic, high-voltage, and high-energy density cathode materials based on LiMNbO 4 (M = Mn, Fe, Co, Ni) composition exhibiting minimal (< 4%) volume strain, during redox process. It confirmed robust crystal structure sustaining volume changes during redox action. Electronic structure indicated band gap (E g ) < 2.0 eV for LiMNbO 4, comparable and/or less than E g range ~ 1.7–2.7 eV or 3.8 eV for respective commercial cathodes LiCoO 2 , LiFePO 4 . The estimated electrochemical voltage is V ~ 5.21, 4.62, 4.05, and 3.63 V for M = Ni, Co, Mn, and Fe, respectively. The highest diffusion barrier of 0.439 eV was achieved for LiMnNbO 4 . Among the four cathodes in LiMNbO 4 , LiNiNbO 4 exhibited the highest energy density of ~ 627 Wh/kg, the least volume strain ~ 1.9%, lower E g ~ 1.85 eV, and bi-directional (along a - and b -axis) diffusion path for Li + ion migration. Graphical abstract Schamatic of all the voltages of LiMNbO 4 , linear correlation between band-gap and voltages, simulated XRD of the phase obatined before and after charging and density of states of all LiMNbO 4